Perbedaan Pretreatment Eco-enzim Kulit Jeruk dan NaOH terhadap Produksi Bioetanol dari Fermentasi Tandan Kosong Kelapa Sawit (TKKS) - Anna Rumyani; Revis Asra; Ashif Irvan Yusuf (PendIPA Journal of Science Education, 2026)
Oil palm empty fruit bunches (OPEFB) are lignocellulosic biomass waste with potential as a second-generation bioethanol feedstock, but their conversion requires a pretreatment atage to open the lignocellulosic structure before hydolysis and fermentation. This study compared the effect of four pretreatment types — distilled water (control, K), NaOH 5% (P1), citrus-peel eco-enzyme (P2), and a combination of NaOH 5% with eco-enzyme (P3) — on the reducing sugar content and bioethanol yield of OPEFB, and evaluated the potential of eco-enzyme as a more environmentally friendly alternative to NaOH. A Completely Randomized Design (CRD) with four treatments and six replications was used. Reducing sugar content was measured semi-quantitatively using the Benedict test (ordinal scale 1–5) and analyzed with the Kruskal-Wallis test, while bioethanol content was measured with an alcohol refractometer following distillation. The highest mean reducing-sugar score was obtained in P1 (4.00), and the Kruskal-Wallis test showed a significant difference among treatments (H = 9.493; df = 3; p = 0.023). However, the resulting bioethanol content did not differ significantly among treatments (H = 3.644; df = 3; p = 0.303), with P1 (16.07%) only slightly higher than P3 (16.03%) and P2 (15.63%). These results indicate that NaOH provided the highest delignification effectiveness, but this was not followed by a significant difference in final bioethanol content, so citrus-peel eco-enzyme has potential as a more environmentally friendly pretreatment alternative that yields bioethanol comparable to NaOH.